The Network of Indigenous Communicators of Peru and the Problem of Indigenous Communication in Peru - Soria Giner, Gonzalo (2025)
In this article we will present a study about the importance of indigenous community radio for preserving, disseminating, and developing the culture of native peoples, and about the difficulties found in Peru for the development of this type of communication projects. To this end, we will first analyze the history of community radio in the country, as well as its legislation regarding communication matters. Subsequently, we will address the question of Peruvian indigenous identity from a brief historical perspective and its current linguistic situation. We will then focus on the particular case of the Network of Indigenous Communicators of Peru (REDCIP) to study their work in the field of indigenous communication in the country. We will approach this question through interviews with network members themselves, as well as through active listening to some of their radio programs. Both the interviews and program listening were conducted between January and March 2023; for this reason, the national crisis situation the country went through during those dates takes on significant relevance, and its analysis forms part of our work.